+0  
 
0
98
2
avatar

Suppose a and b are integers. How many solutions are there to the equation ab = 2a + 3b?

Guest Sep 27, 2017
Sort: 

2+0 Answers

 #1
avatar
0

a*b=2a + 3b

a = -3 and b = 1

a = 0 and b = 0

a = 1 and b = -1

a = 2 and b = -4

a = 4 and b = 8

a = 5 and b = 5

a = 6 and b = 4

a = 9 and b = 3

Guest Sep 27, 2017
 #2
avatar+79786 
+1

ab  = 2a + 3b

 

Square both sides

 

a^2b^2  = 4a^2 + 12ab + 9b^2   rearrange as

 

[ 4-b^2]a^2 + [ 12b]a + 9b^2  = 0

 

Setting this up as a quadratic and solving for  a, we have that

 

a  =  -12b ±√ [  (-12b)^2 - 4 (4 - b^2)( 9b^2) ]

        ________________________________

                    2 [ 4 - b^2]

 

a  =  -12b ±√ [  144b^2  - 144b^2  + 36b^4 ]

        _______________________________

                      2 [ 4 - b^2 ]

 

a =    -12b  ± 6b^2

          ___________

              2 [ 4 - b^2 ]

 

 

a  =     6b [  -2  ± b ]

           ___________

             2 [ 4 - b^2 ]

 

a  =   3b [ -2  ± b ]

        _____________         

          (2 + b)  (2 - b)

 

Choosing        a  =       3b [ -2 - b]                           -3b [ 2 + b]                     -3b

                                  __________     =                _____________      =        ___

                                  (2 + b) (2 -b)                         (2 + b) (2 -b)                    2 -b

 

Will  produce all the possible integer answers                       

 

 

Simplifying, we have that            

 

                                                                                                                            

a  =  -3b               3b                                     

       _____   =     ____                                                                            

        2 - b             b - 2                   

 

 

Dividing this fraction produces :

 

a =   3  +    6                                                                                                      

               ____                                                                              

                b - 2                                                                                       

 

And when   b  =     8      5      4     3    1    0    -1   -4

                   a =      4      5      6     9   -3    0     1    2

 

So.........( a, b)  =  (2, -4), (1, -1), (0, 0), (-3, 1), (9, 3), (6,4), (5,5)  and (4,8)

 

 

 

cool cool cool

 

 

                  

 

 

a  = 

CPhill  Sep 27, 2017
edited by CPhill  Sep 27, 2017

14 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details